2002
DOI: 10.1002/ptr.951
|View full text |Cite
|
Sign up to set email alerts
|

Studies on essential oils: Part 10; Antibacterial activity of volatile oils of some spices

Abstract: The essential oils extracted from the seeds of seven spices, Anethum graveolens, Carum capticum, Coriandrum sativum, Cuminum cyminum, Foeniculum vulgare, Pimpinella anisum and Seseli indicum have been studied for antibacterial activity against eight pathogenic bacteria, causing infections in the human body. It has been found that the oil of C. capticum is very effective against all tested bacteria. The oil of C. cyminum and A. graveolens also gave similar results. These oils are equally or more effective when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
125
0
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(137 citation statements)
references
References 4 publications
7
125
0
5
Order By: Relevance
“…Experimental studies have shown that cumin possesses antimicrobial (Agnihotri & Vaidya, 1996;Singh et al, 2002), anticarcinogenic (Aruna & Sivaramakrishnan, 1992;Gagandeep et al, 2003), antidiabetic (Dhandapani et al, 2002;Sushruta et al, 2006), anti-inflammatory (Srivastava, 1989;Shivakumar et al, 2010), antioxidant (Saito et al, 1976;Huang et al, 1981;Satyanarayana et al, 2004), antinociceptive (Sayyah et al, 2002), antitussive (Boskabady et al, 2006), antiepilepsy (Khatibi et al, 2008), hypocholesterolemic (Shirke & Jagtap, 2009), antifungal (Pai et al, 2010) properties, and improves chick production in poultry industry (Al-Kassi, 2010).…”
Section: Original Articlementioning
confidence: 99%
“…Experimental studies have shown that cumin possesses antimicrobial (Agnihotri & Vaidya, 1996;Singh et al, 2002), anticarcinogenic (Aruna & Sivaramakrishnan, 1992;Gagandeep et al, 2003), antidiabetic (Dhandapani et al, 2002;Sushruta et al, 2006), anti-inflammatory (Srivastava, 1989;Shivakumar et al, 2010), antioxidant (Saito et al, 1976;Huang et al, 1981;Satyanarayana et al, 2004), antinociceptive (Sayyah et al, 2002), antitussive (Boskabady et al, 2006), antiepilepsy (Khatibi et al, 2008), hypocholesterolemic (Shirke & Jagtap, 2009), antifungal (Pai et al, 2010) properties, and improves chick production in poultry industry (Al-Kassi, 2010).…”
Section: Original Articlementioning
confidence: 99%
“…Carum carvi (CC) (Apiaceae), locally known as 'Kala Jira'. It posses antibacterial [5], antiulcerogenic [6], antitumor [7], antiproliferative [8] and antihyperglycemic [9].…”
Section: Introductionmentioning
confidence: 99%
“…The medicinal component of the plant is Cumin oil extracted from the ripe fruit. Cumin is used as stomachic, diuretic, carminative, stimulant, astringent, emmenagogic, antispasmodic and antifungal 81 . In Algeria it is now used mainly in veterinary medicine, as a carminative, but it remains a traditional herbal remedy.…”
Section: Cuminum Cyminum L Therapeutic Uses and Spasmolytic Activitiesmentioning
confidence: 99%